Ecotracer: analyzing concentration of contaminants and radioisotopes in an aquatic spatial-dynamic food web model. (January 2018) - Walters, William J.; Christensen, Villy
Abstract: Ecotracer is a tool in the Ecopath with Ecosim (EwE) software package used to simulate and analyze the transport of contaminants such as methylmercury or radiocesium through aquatic food webs. Ecotracer solves the contaminant dynamic equations simultaneously with the biomass dynamic equations in Ecosim/Ecospace. In this paper, we give a detailed description of the Ecotracer module and analyze the performance on two problems of differing complexity. Ecotracer was modified from previous versions to more accurately model contaminant excretion, and new numerical integration algorithms were implemented to increase accuracy and robustness. To test the mathematical robustness of the computational algorithm, Ecotracer was tested on a simple problem for which we know an analytical solution. These results demonstrated the effectiveness of the program numerics. A much more complex model, the release of the cesium radionuclide 137 Cs from the Fukushima Dai-ichi nuclear accident, was also modeled and analyzed. A comparison of the Ecotracer results to sampled 137 Cs measurements in the coastal ocean area around Fukushima show the promise of the tool but also highlight some important limitations. Highlights: Ecotracer integrates modeling of food web and contaminant dynamics into the open source Ecopath with Ecosim model framework. Ecotracer was updated with corrected models and improved numerics. The Ecotracer model was tested on an analytical model for numerical validation. Cs-137 transport and assimilation near Fukushima Dai-ichi was simulated. Ecotracer has limited hydrodynamic modeling capabilities, but can be linked to other models that predict flow patterns.